Management and Personnel: Whitehead, Dickinson, Brower - Feldman, Herman; Whitehead, T. N.; Dickinson, Z. Clark; Brower, F. Beatrice (Quarterly Journal of Economics, 1937)
Journal Article Management and Personnel: Whitehead, Dickinson, Brower Get access Herman Feldman Herman Feldman The Amos Tuck School of Administration and Finance, Dartmouth College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 51, Issue 4, August 1937, Pages 699–704, https://doi.org/10.2307/1881686 Published: 01 August 1937